Chronic physical conditions and risk for perinatal mental illness: A population-based retrospective cohort study. - Hilary K Brown; Andrew S Wilton; Joel G Ray; Cindy-Lee Dennis; Astrid Guttmann; Simone N Vigod (PLoS Medicine, 2019)
Background One in 5 women experience mental illness in pregnancy or post partum. Universal preventive interventions have not lowered the incidence of perinatal mental illness, perhaps because those at highest risk were not targeted. Outside of pregnancy, chronic physical conditions are known to confer increased risk for mental illness. Our objective was to examine the association between chronic physical conditions and risk of perinatal mental illness. Methods and findings We conducted a population-based retrospective cohort study using linked health administrative data sets in Ontario, Canada, in 2005 to 2015. We compared 77,385 women with chronic physical conditions to 780,619 women without such conditions, all of whom had a singleton live birth. Excluded were women with a mental illness diagnosis within 2 years before pregnancy. Chronic physical conditions were captured using the Agency for Healthcare Research and Quality Chronic Condition Indicator, applied to acute healthcare encounters in the 2 years before pregnancy. The outcome was perinatal mental illness, defined by a mental illness or addiction diagnosis arising between conception and 365 days post partum. The outcome was further defined by timing (prenatal or post partum) and specific diagnosis (psychotic disorder, mood or anxiety disorder, substance use disorder, self-harm, or other). Modified Poisson regression generated relative risks and 95% confidence intervals (CIs), adjusted for age, parity, rural residence, income quintile, and remote history of mental health care. Women in the cohort had an average age of 29.6 years (standard deviation 5.4), 44.2% were primiparous, 11.0% lived in a rural area, 40.1% were in the lowest 2 income quintiles, and 47.9% had a remote history of mental health care. More women with (20.4%) than without (15.6%) a chronic physical condition experienced perinatal mental illness-an adjusted relative risk (aRR) of 1.20 (95% CI 1.18-1.22, p < 0.0001). The aRRs were statistically significant for mental illness in pregnancy (1.12, 95% CI 1.10-1.15, p < 0.0001) and post partum (1.25, 95% CI 1.23-1.28, p < 0.0001). Psychotic disorders (aRR 1.50, 95% CI 1.36-1.65, p < 0.0001), mood or anxiety disorders (aRR 1.19, 95% CI 1.17-1.21, p < 0.0001), substance use disorders (aRR 1.47, 95% CI 1.34-1.62, p < 0.0001), and other mental illness (aRR 1.68, 95% CI 1.50-1.87, p < 0.0001) were more likely in women with than without chronic physical conditions, but not self-harm (aRR 1.14, 95% CI 0.87-1.48, p = 0.34). The study was limited by reliance on acute health care encounters to measure chronic physical conditions and the inability to capture undiagnosed mental health problems. Conclusions Findings from this study suggest that women with a chronic physical condition predating pregnancy may be at heightened risk of developing mental illness in the perinatal period. These women may require targeted efforts to lower the severity of their condition and improve their coping strategies and supports in pregnancy and thereafter.